Kesejajaran Realitas Ra’aytu Ramallah karya Mourid Barghouti dan Sejarah Palestina (Tinjauan Strukturalisme Genetik) - Dadang Ismatullah (Alfaz (Arabic Literatures for Academic Zealots), 2022)
This article tries to approach the conflict of Palestine through the novel Rsa'aytu Ramallah by Maorid Barghouti as seeking its parallel realities with historical facts. In so doing, the genetical components are to be analyzed by employing the Genetical Structaralism theory of Lucien Goldmann. The genetic of the novel can be seen in the parallelism between the literary facts and the socio-historical facts along the story. Thus, the novel not only comprises a mere fiction, but also along history of Palestine-Israel wars during the life of Barghouti. The author's worldview captures several crucial issues, such as the impacts of the war for Palestinians -mostly the immigrants among them-, the unstable politics that does not benefit the Palestinians interest, and gender iniquity which still exists in Palestine.